2018
DOI: 10.1002/slct.201702867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Hydroxide Pretreatment of NiOx Cathodes on the Performance of Squaraine‐Sensitized p‐Type Dye‐Sensitized Solar Cells

Abstract: Squaraines are full‐organic dyes employed as sensitizers in p‐type dye‐sensitized solar cells (p‐DSSC). Their absorption spectrum shows a wide tunability that ranges from visible to NIR. Sensitization in the NIR region is crucial for exploiting a particularly intense portion of the solar spectrum. In this work three squaraines will be presented and tested as sensitizers in NiO‐based p‐type DSSC O4_C2, O4_C4 and O4_C12). The structures of the dyes differ for the length of the alkyl side chain (C2, C4 and C12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In all the experiments, the electrolyte solution was LiClO4 0.2 M in ACN (Acetonitrile). All figures have been plotted with the application Kaleidagraph 3.6, and their photoelectrochemical characterization has been already described in previous works [36,85,86]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the experiments, the electrolyte solution was LiClO4 0.2 M in ACN (Acetonitrile). All figures have been plotted with the application Kaleidagraph 3.6, and their photoelectrochemical characterization has been already described in previous works [36,85,86]. …”
Section: Methodsmentioning
confidence: 99%
“…The structures of the nine dyes here employed as sensitizers of NiO are reported in the Supplementary Materials ( Figures S1-S3). The colorants here considered are P1 [75][76][77][78], Fast Green (FG) [79,80], erythrosine B (ERY) [3,[81][82][83], the series of the differently substituted squaraines DS_35, DS_44, and DS_46 [84,85], and the series of squaraines VG_1, VG_10, and VG_11, which differ to the extent of electronic conjugation [86].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative route is the direct modification of the photocathode. In a previous paper we showed that the treatment of NiO surface with soda has a twofold effect: it reduces the surface concentration of superficial Ni 3+ sites and passivates the NiO surface prior sensitization 22 . The success of this method has been confirmed by the achievement of a less dark film.…”
Section: Introductionmentioning
confidence: 99%
“…Some of us have previously reported the effect of a soda pretreatment on a NiO electrode surface on the photoelectrochemical properties of squaraine-based p-type DSC (Bonomo et al, 2018b). The chemisorption of the hydroxyl moieties on the NiO surface has been shown to lower the dye-loading leading to a lower photocurrent density.…”
Section: Introductionmentioning
confidence: 99%
“…Here we introduce the synthesis and the applications of a new squaraine dye (VG21-C12) as a sensitizer for p-DSC in comparison to the derivative O4-C12 as a reference (Figure 1) (Bonomo et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%